Prescribing of inhaled corticosteroids-containing and non-inhaled corticosteroids therapy in patients with chronic obstructive pulmonary disease at a Malaysian tertiary care center - Lukman Nul Hakim Md Khairi,, Mohd Shahezwan Abd Wahab,, Norkasihan Ibrahim, Norhaya Mohd Razali, Nur Wahida Zulkifli (Journal of Applied Pharmaceutical Science, 2023)
Inhaled corticosteroids (ICS) are a common pharmacotherapy option for chronic obstructive pulmonary disease (COPD) patients. However, previous reports showed that ICS has been overprescribed. This study aimed to identify the prevalence of and factors associated with the prescribing of ICS-containing and non-ICS therapy among a sample of COPD patients at a Malaysian hospital and to examine the patterns of COPD inhaled therapy prescriptions among the patients in the years 2017–2020. The study also aimed to determine the proportion of ICS-containing therapy users that were suitable for ICS withdrawal. In total, 153 COPD patients who were using an ICS-containing or a non-ICS therapy within the study period (2017–2020) were included. Most patients were male (91.5%) and Malays (96.1%). Overall, 45.1% of the patients had been prescribed an ICS-containing therapy. A history of moderate exacerbations, presence of concurrent asthma, and eosinophilia were significantly associated with ICS-containing therapy prescribing. A decreasing trend in ICS-containing therapy prescribing from 2017 to 2020 was observed. During the most recent clinic follow-up, 77 patients were ICS users and 26% of them could benefit from ICS withdrawal. Measures to improve ICS-containing therapy prescribing and de-prescribing are warranted.